Mechatronic Modeling of Real-Time Wheel-Rail Contact - Bosso, Nicola; Spiryagin, Maksym; Gugliotta, Antonio; Somà, Aurelio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Real-time simulations of the behaviour of a rail vehicle require realistic solutions of the wheel-rail contact problem which can work in a real-time mode. Examples of such solutions for the online mode have been well known and are implemented within standard and commercial tools for the simulation codes for rail vehicle dynamics. This book is the result of the research activities carried out by the Railway Technology Lab of the Department of Mechanical and Aerospace Engineering at Politecnico di Torino. This book presents work on the project for the development of a real-time wheel-rail contact model and provides the simulation results obtained with dSpace real-time hardware. Besides this, the implementation of the contact model for the development of a real-time model for the complex mechatronic system of a scaled test rig is presented in this book and may be useful for the further validation of the real-time contact model with experiments on a full scale test rig.
Introduction -- Review of Wheel-Rail Contact Models -- RollerRigs -- Design of Scaled Roller Rigs -- Contact Model -- Real-Time Simulation of the Contact Model -- Example of Real-Time Application for Scaled Test Rig.
Keywords: Vibration; Dynamical systems; Dynamics; Mechatronics; Machinery; Vibration, Dynamical Systems, Control; Mechatronics; Machinery and Machine Elements